PENGARUH PENYAJIAN ALA BENTO TERHADAP ASUPAN GIZI PASIEN DI BANGSAL ANAK RSUP Dr. SARDJITO - , FATWA RULI INDRIASTUTI, Susetyowati, DCN, M.Kes ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: malnutrition in hospitals can occur due to many factors. The most dominant factor affecting the risk of malnutrition is food intake (Nazarena, 2008). Energy intake (42.9%) and protein intake (38.5%) in the pediatric ward of Dr. Sardjito Hospital is still low (Oktaviani, 2009). Lack of nutrition in the hospital is due to lack of patient acceptability and perception (Wachyudin, 2009), while the patient's perception influenced by the quality of the food is also influenced by the appearance (Almatsier, 1992). According to Moehyi (1999) plate dressing can be used as an attempt to improve patientâs acceptance, so that the nutrient intake also increase. Objectives: This study aims to determine the effect of bentoâs modification on nutrition intake in the pediatric ward of Dr. Sardjito Hospital, Yogyakata. Methods: This research is a quasi experimental study. Respondents are divided into two groups